Reticulocyte parameters for monitoring anemia in patients with chronic kidney disease on peritoneal dialysis - Merlin,Júlio C. (2021)
ABSTRACT Introduction: Anemia is a complication with impact on morbidity and mortality in chronic kidney disease (CKD) patients. Current markers for the diagnosis and monitoring of anemia in CKD are limited by the interrelation between erythropoiesis, iron stores, inflammation, and the resistance to treatment with erythropoiesis stimulant agents (ESA). Objective: The aim of this study was to analyze the role of immature reticulocyte fraction (IRF) and hemoglobin concentration in reticulocytes (RET-He) by the hematology analyser Sysmex XN-5000 in the monitoring of CKD anemia in peritoneal dialysis patients. Methods: This was a prospective, observational multicenter study which compared IRF and RET-He with parameters recommended by the guidelines. Inflammatory biomarkers were analyzed by the Luminex® Multiplexing Instruments system. Thirty-five patients (59 ± 13 years old; 51% men) were included in the analysis. Results: Hemoglobin was 12.2 ± 2 g/dl; 87% had resistance to ESA. Patients with erythropoietin resistance index (ERI) in the upper quartile presented a significantly higher of IRF and a lower percentage of iron deficiency (12%) compared to ferritin (82%) and transferrin saturation index (STI) (51%). Interleukin-6 (IL-6) levels correlated with the percentage of medium fluorescence reticulocyte (MFR) (r = 0.45, p < 0.03). Hemoglobin values after 60 and 180 days were consistently higher in the group of patients with a IRF% lower than 10.5. Conclusion: IRF and RET-He may add value in the iron deficiency investigation, as well as in the identification of patients with ERI. Due to the restricted number of patients analyzed in this study, future studies should be encouraged in larger populations and with prospective follow-up, to validate our findings.